Antimicrobial evaluation of the crude extract of symbiotic fungi from marine sponge Reniera japonica (Bangladesh Journal of Pharmacology, 2018)
Marine sponge-derived microbes are one of the rich sources of bioactive natural products with a broad spectrum of bioactivities. The present work focuses on the isolation and antimicrobial screening of the marine sponge-associated fungi from Reniera japonica MNP-2016. The results indicated that five fungi (L1-2, L2-1, L4, L8-1 and L14) were successfully isolated. Bioassay tests showed that only strain L14 had strong inhibitory effect on the pathogens, Staphyloccocus aureus, Escherichia coli and Candida albicans. 18S rDNA sequence analysis indicated that strain L14 was ascribed to Aspergillus genus. To the best of our knowledge, this work was the first report on the isolation and antimicrobial evaluation of fungi from R. japonica.Video Clip of Methodology:1 min 13 sec:   Click to watch